156 Motor neurones subtypes resistant to degeneration in amyotrophic lateral sclerosis show distinct synaptic characteristics across species. Issue 3 (9th February 2012) - Brockington, A; Ning, K; Heath, P; Wood, E; Malik, K; Fusi, N; Wharton, S; Ince, P G; Shaw, P J
Abstract : A consistent clinical feature of amyotrophic lateral sclerosis (ALS) is the sparing of eye movements and the function of external sphincters, with corresponding preservation of motor neurones (MNs) in the brainstem oculomotor nuclei, and of Onuf's nucleus in the sacral spinal cord. Studying the differences in properties of neurones that are vulnerable and resistant to the disease process in ALS may provide insights into the mechanisms of neuronal degeneration, and identify targets for therapeutic manipulation. We used microarray analysis to determine the differences in gene expression between oculomotor and spinal MNs, isolated from the spinal cord of neurologically normal controls, using laser capture microdissection. We have compared these transcriptional profiles to those of oculomotor nuclei and spinal cord from rat and mouse, obtained from the GEO omnibus database. We show that oculomotor neurones have a distinct transcriptional profile, with significant differential expression in isolated human MNs of 1757 named genes (q<0.001). Marked differences are seen, across the three species, in genes with a function in synaptic transmission, including several glutamate and GABA receptor subunits. We have confirmed the functional significance of this, using patch clamp recording in acute spinal and brainstem slices. We show significant differences in the inward calcium current induced by agonists at these receptors, which would predict an altered susceptibility to excitotoxicity.